Return of the State and attempts of centralisation in Italy - Paolo Perulli (Métropoles)
The paper analyses the unresolved question of urban and metropolitan governance in Italy in the light of current trends towards re-centralization at national level of policies and resources. This is part of a broader global-local issue. While the “global” has received an extraordinary recognition, a mistrust towards the “local” as and obstacle to development continues to be part of the political and economic dominant approaches in Italy. On this base, weaknesses and strengths of Italian regional and local policies are sketched. There is a growing need to conceive the “local” in a more universal way: the city as a complete society open to cross-border relations with other placesand cultures, and a node of wider global city-regions and networks. An approach towards macroregional governance in the framework of European place-based reform of territorial cohesion is finally proposed.